(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article describes the role and importance of accuracy of movement in the structure of physical qualities, the organization of experiments to improve the physical development of tennis girls of different ages and genders and their physical and special training.